Distal Femoral Cortical Hypertrophy after Hip Arthroplasty Using a Cementless Double-Tapered Femoral Stem. (December 2016) - Cho, Yoon Je; Chun, Young Soo; Rhyu, Kee Hyung; Baek, Jong Hun; Liang, Hu
Purpose: To review 437 hips in 404 patients who underwent total hip arthroplasty (THA) or hemiarthroplasty using the Accolade TMZF stem to determine the incidence and risk factors of distal femoral cortical hypertrophy (DFCH). Methods: Records of 437 hips in 169 men and 235 women aged 26 to 100 (mean, 65.7) years who underwent THA (n=293) or hemiarthroplasty (n=144) using the Accolade TMZF femoral stem by 2 senior surgeons and were followed up for a mean of 54.7 months were reviewed. Clinical outcome was assessed using the modified Harris Hip Score and visual analogue score for pain. Proximal femoral geometry and canal flare index were assessed on preoperative radiographs, and DFCH, stem position, subsidence, loosening, and stress shielding were assessed on postoperative radiographs according to the Gruen zone. Results: Of 437 hips, 27 (6.2%) developed DFCH and 410 did not. Hips with DFCH had a higher incidence of thigh pain (18.5% vs. 2.2%, p<0.001) and earlier onset of thigh pain (12.3 vs. 20.8 months, p=0.015), compared with those without. Nonetheless, all femoral stems were well-fixed, and no osteolysis or loosening was detected. The 2 groups achieved comparable clinical outcome in terms of Harris Hip Score and pain. The mean canal flare index was higher in hips with than without DFCH (3.706 vs. 3.294, p=0.002). The mean vertical subsidence of the femoral stem was lower in hips with than without DFCH (1.5 vs. 3.4 mm p<0.001). Subsidence negatively correlated with the canal flare index (correlation coefficient= −0.110, p=0.022). The incidence of the DFCH increased with each unit of increment in canal flare index (odds ratio [OR]=1.828, p=0.043) and each year younger in age (OR=0.968, p=0.015). Conclusion: The incidence of DFCH in hips with the Accolade TMZF stem was 6.2%. Patients with a higher canal flare index and younger age had a higher incidence of DFCH. Nonetheless, DFCH did not affect clinical outcome or femoral stem stability.